Prevalence of metabolic syndrome and the association with sociodemographic characteristics in adult population of Banja Luka - Petrović, Verica; Tešanović, Gordana; Stanivuk, Ljiljana (Vojnosanitetski pregled, 2020)
Background/Aim. Metabolic syndrome (MS) is a cluster of metabolic and hemodynamic disorders that increase the risk of developing atherosclerotic cardiovascular diseases and type 2 diabetes mellitus. The aim of this study was to determine the prevalence of MS and its components in adult population of Banja Luka and association with sociodemographic characteristics. Methods. A total of 685 participants (348 men and 337 women), aged 18 years and over, were analyzed. The diagnosis of the MS was based on definition set by the International Diabetes Federation (IDF). Results. The prevalence of the MS was high (37.5%), slightly higher in women (38.3%) than in men (36.8%), but without statistically significant difference (p = 0.686). Prevalence of each individual component of the MS in the study group was over 30% (systolic blood pressure ≥ 130 mmHg – 42.0%; diastolic blood pressure ≥ 85 mmHg – 31.0%; triglycerides ≥ 1.7 mmol/L – 36.1%; high density lipoprotein (HDL) cholesterol ˂ 1.03 for men and ˂ 1.29 for women – 31.2%; glucose ≥ 5.6 mmol/L – 32.8%; central obesity ≥ 94 cm male and ≥ 80 cm female – 62.6%). The prevalence of the MS was not associated with gender, but with age. A number of participants increased with incresed age in the group with the MS with statistically significant difference compared to the group without the MS. The study showed an association between level of education and the MS. Low level of education was associated with the appearance of the MS with statistically significant differences (df = 3; p = 0.013). Association between level of education and the MS was shown in women (df = 3; p = 0.000), but not in men (df = 3; p = 0.883). Retirees and housewives were significantly present in the group with the MS, students and unemployed in the group without the MS, while employed participants showed no statistically significant difference. Conclusion: The MS was diagnosed in over one-third of adults in Banja Luka. Prevalence of MS was not associated with gender, but it was associated with age, level of education as well as with some categories of employment.